Toxicity of pathogenic ataxin-2 in Drosophila shows dependence on a pure CAG repeat sequence. - McGurk, L.; Rifai, O.M.; Shcherbakova, O.; Perlegos, A.E.; Byrns, C.N.; Carranza, F.R.; Zhou, H.W.; Kim, H.J.; Zhu, Y.; Bonini, N.M. (Human Molecular Genetics, 2021)
Spinocerebellar ataxia type 2 is a polyglutamine (polyQ) disease associated with an expanded polyQ domain within the protein product of the ATXN2 gene. Interestingly, polyQ repeat expansions in ATXN2 are also associated with amyotrophic lateral sclerosis (ALS) and parkinsonism depending upon the length of the polyQ repeat expansion. The sequence encoding the polyQ repeat also varies with disease presentation: a pure CAG repeat is associated with SCA2, whereas the CAG repeat in ALS and parkinsonism is typically interrupted with the glutamine encoding CAA codon. Here, we asked if the purity of the CAG sequence encoding the polyQ repeat in ATXN2 could impact the toxicity of the ataxin-2 protein in vivo in Drosophila. We found that ataxin-2 encoded by a pure CAG repeat conferred toxicity in the retina and nervous system, whereas ataxin-2 encoded by a CAA-interrupted repeat or CAA-only repeat failed to confer toxicity, despite expression of the protein at similar levels. Furthermore, the CAG-encoded ataxin-2 protein aggregated in the fly eye, while ataxin-2 encoded by either a CAA/G or CAA repeat remained diffuse. The toxicity of the CAG-encoded ataxin-2 protein was also sensitive to the translation factor eIF4H, a known modifier of the toxic GGGGCC repeat in flies. These data indicate that ataxin-2 encoded by a pure CAG versus interrupted CAA/G polyQ repeat domain is associated with differential toxicity, indicating that mechanisms associated with the purity of the sequence of the polyQ domain contribute to disease.